Assessment of the association between the components of the metabolic syndrome and the pathology of dental hard tissues and inflammatory periodontal diseases - V. O. Senina; I. N. Usmanova; I. A. Lakman; L. P. Gerasimova; A. N. Ishmukhametova; N. A. Makarova; V. A. Berezin (Эндодонтия Today, 2024)
AIM. Is to assess the interaction between the pathology of carious and non-carious dental hard tissues, inflammatory periodontal diseases and components of the metabolic syndrome (MS).MATERIALS AND METHODS. A retrospective observational and comprehensive dental examination of 105 patients with MS has been performed. The complex of dental examination included analysis of complaints, anamnesis, assessment of the condition of dental hard tissues, and periodontal tissues. As a result of retrospective observational analysis, 3 clinical groups have been formed as follows: 2 main clinical groups with MS with impaired carbohydrate metabolism, and with type 2 diabetes mellitus, as well as a group with MS without impaired carbohydrate metabolism (experimental group).RESULTS. The caries prevalence rate in patients of the 1st and 2nd main clinical groups according to WHO criteria is high, that is 92.5% and 97.3%, (р < 0.001), the average caries intensity level according to the DMF index (Decayed, Missing, Filled index) corresponds to the criterion of high and very high (< 0.001), there is a prevalence of increased abrasion in 76.3% and 51.0% (р < 0.05), hyperesthesia in 69.2% and 67.3%, wedge-shaped defects of hard tissues in 57.7% and 46.2% (р < 0.001), in 34.6% and 80.8% of cases there is a prevalence of chronic periodontitis (р < 0.001) as compared to the experimental group. In this category of patients, the median value of hygienic (SOHI / Simplified Oral Health Index) and periodontal indices of SBI, PI, periodontal pocket depth have been statistically and significantly different from the experimental group patients according to the Kruskal Wallis Test, р < 0.01.CONCLUSIONS. Thus, in patients with metabolic syndrome with impaired carbohydrate metabolism and type 2 diabetes mellitus, the prevalence of carious and non-carious tooth hard tissue pathology and periodontal inflammatory diseases is observed among the main dental diseases. The data obtained require an interdisciplinary approach in the development and planning of early qualitative diagnostic and treatment and preventive interventions maneuvers in conjunction with a dentist, endocrinologist, and a therapist.